On the assessment of thermo-mechanical degradability of multi-recycled ABS polymer for 3D printing applications - Charles, Amal (2019)
Although additive manufacturing (AM) has offered proven ability to reduce waste when compared with traditional manufacturing techniques, however, AM processes such as fused filament fabrication (FFF) still poses some negative environmental and economic aspects in terms of generated waste. This waste comes from rafts, supports, or bases that are parts of the supporting structure necessary in the construction of proper 3D-printed parts. In addition, another source of waste comes from jobs that failed due to a variety of reasons as is common with 3D printing. One possible way to minimize the negative effect is to recycle this waste material. Through the usage of commercially available cutting mills and extruder equipment that are easily procurable, it is possible to recycle the waste and reuse it as a filament. In this context, this paper aims to experimentally investigate the feasibility of recycling 3D printing waste material, namely of ABS material which is a popular 3D printing material and to evaluate changes in the mechanical behaviour after each recycling cycle, while taking the performance of the virgin material as a reference point. The mechanical behaviour of the recycled materials was assessed as a function of obtainable tensile strength, toughness and thermal transition. The results show that the ABS filament shows great promise for recycling at least once and could lead to significant material and cost savings. In this work, it is possible to observe how many times ABS can be recycled and used as filament, without adding virgin material.